التكييف الفقهي لمسؤولية الأضرار الناتجة عن قرارات الذكاء الاصطناعي - ليفة، ميلود (انطاليا - تركيا, 2025)
يتناول هذا البحث بالدراسة الفقهية المقارنة مسألة مسؤولية الأضرار الناتجة عن قرارات الذكاء الاصطناعي، بوصفها من القضايا المعاصرة التي تمس جوهر العلاقة بين الإنسان والآلة؛ فعندما تتسبب سيارة ذاتية القيادة في حادث، أو يخطئ نظام تشخيص طبي آلي في تقديره، أو يؤدي قرار خوارزمية مالية إلى خسائر فادحة، يثور التساؤل الجوهري: على من تقع المسؤولية؟ هل هو المبرمج الذي صمم الخوارزمية، أم الشركة المصنّعة، أم المستخدم النهائي، أم الكيان الاصطناعي ذاته؟ سعى البحث إلى تكييف هذه المسؤولية فقهياً استنادًا إلى القواعد الكلية والأصول الشرعية، من خلال تحليل أطراف العلاقة: المبرمج، والشركة المنتجة، والمستخدم، والغير؛ وقد خلص إلى أن الذكاء الاصطناعي يُعدّ آلةً لا شخصيةً مستقلة، وأن الضمان الشرعي يُنسب إلى الإنسان بحسب درجة المباشرة أو التسبب، وفقاً لقواعد الضمان المقررة في الفقه الإسلامي؛ كما أظهر البحث قدرة الفقه الإسلامي على استيعاب المستجدات التقنية من خلال مرونته وقابليته للاجتهاد التنزيلي، واقترح إطاراً تشريعياً يوازن بين الابتكار والمسؤولية، ويؤسس لضمان عادل يراعي مقاصد الشريعة في حفظ الأنفس والأموال. Abstract: This research presents a comparative jurisprudential study on the liability for damages resulting from decisions made by Artificial Intelligence (AI)—a contemporary issue that lies at the heart of the relationship between humans and machines. When an autonomous vehicle causes an accident, an automated medical diagnostic system errs, or a financial algorithmic decision leads to significant losses, the fundamental question arises: who bears legal liability? Is it the programmer who designed the algorithm, the manufacturer, the end user, or the AI system itself? The study seeks to provide a juristic classification (takyīf fiqhī) of this liability based on the universal maxims and principles of Islamic law (al-qawāʿid al-fiqhiyyah), by analyzing the roles of the programmer, the manufacturer, the user, and third parties. It concludes that AI should be considered a tool rather than an autonomous legal entity, and that liability under Islamic law (ḍamān) is attributed to human agents according to the degree of direct causation (mubāsharah) or indirect causation (tasabbub), in line with the established rules of Islamic jurisprudence. Furthermore, the study demonstrates the flexibility of Islamic law in accommodating modern technological developments through contextual ijtihād tanzīlī, and proposes a legislative framework that balances innovation with accountability while upholding the higher objectives of Sharīʿah (Maqāṣid al-Sharīʿah), particularly the preservation of life and property.
دراسة فقهية مقارنة
Intervention
Keywords: الذكاء الاصطناعي; التكييف الفقهي; المسؤولية; الضمان; الضرر; Artificial Intelligence (AI); Juristic Classification (Takyīf Fiqhī); Liability; Ḍamān (Islamic Liability/Indemnity); Harm